PENANGANAN LIMBAH ORGANIK MENJADI BAHAN BAKU PAKAN DALAM PRODUKSI MAGGOT UNTUK SUMBER PROTEIN PAKAN IKAN BUDIDAYA SEBAGAI IMPLEMENTASI KONSEP BLUE ECONOMY - V. Limmon, Gino; D. Manuputty, Gratia; N. M. Fendjalang , Sophia (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Hein Namotemo, 2022)
Aquaculture is currently one of the leading sectors. In practice, fish feed is often a problem because the quantity and price often depend on the season and the high production costs for feed. For this reason, alternative feeds and raw feed materials have been developed, which are considered in line with the blue economy concept that the government is promoting to address existing problems, namely magot (black soldier fly larvae), so that not only is the economy the goal, but the environment is also maintained. Using organic waste and providing commercial feed opportunities embody the concept of a blue economy in fish farming by utilizing magot feed. This Community Service activity aims to introduce and train the concept of cultivating and commercializing magot products as feed. The activities involving mariculture practitioners were carried out at the Maritime and Marine Science Center of Excellence at Pattimura University, Ambon, with several activities starting from preparation, implementation, and evaluation. In the early stages, magot cages and various materials needed for cultivation were prepared, including fermented fly-feed products. Based on the evaluation results, there was an increase in knowledge, reaching 85.71% -100%, while the increase in skills ranged from 90.48% -100%. The combination of lecture methods and direct training can provide effective results because participants can listen, discuss, and practice directly.